Edukasi Stunting Melalui Audiovisual Dan Leaflet Meningkatkan Pengetahuan Dan Sikap Ibu Hamil - Dina Ikhya Unnisa; Ratnawati Ratnawati; Jamil Anshory; Nina Mardiana (Poltekkes Kemenkes Semarang, 2023)
Background : Stunting can be caused by a lack of proper understanding and attitudes related to nutrition and health during pregnancy. Therefore, an educational program is needed to improve the understanding and attitudes of pregnant mothers, such as through audiovisual media.Purpose : to determine the effect of stunting education using audiovisual media on the knowledge and attitudes of pregnant women in the Mangkupalas Health Center Working Area.Methods : This quasi-experimental study used a pre-post test design with a control group. A total of 34 participants were selected through purposive sampling, with 16 in the intervention group and 18 in the control group. The research was conducted at Mangkupalas Health Center from April 26 to May 31, 2023. Data were collected through questionnaires, and the intervention group received education through audiovisual media for 8 minutes, while the control group received material in the form of leaflets. Data analysis was conducted using the Wilcoxon test and the Mann Whitney test.Result : The results of the study indicate that stunting education using audiovisual media successfully increased the knowledge of pregnant women (p = 0.013) but had no impact on their attitudes (p = 0.083). Difference analysis showed no significant difference in knowledge improvement after receiving education through audiovisual media compared to leaflets (p = 0.687).Conclusion: Stunting education through audiovisual media influences the knowledge of pregnant women but does not significantly impact their attitudes